2019
DOI: 10.1111/rda.13575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n‐3 PUFA‐rich fish oil supplementation during late gestation on kidding, uterine involution and resumption of follicular activity in goat

Abstract: We have shown that dietary supplementation of n‐3 polyunsaturated fatty acid (n‐3 PUFA)‐rich fish oil (FO) around the breeding time improved the utero‐ovarian functions in the goat. Here, we investigated the effect of FO supplementation during the periparturient period on serum n‐3 PUFA, prostaglandin F2α metabolite (PGFM), placental expulsion, uterine involution, resumption of oestrus and neonatal vigour. Rohilkhandi goat in advanced gestation (n = 16) was divided into two equal groups. One group was suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that in ruminants, rumen microbes may hinder the transfer of dietary LA to semen because they hydrogenate LA ( 81 ). However, recent studies have shown that feeding additional LA results in significantly increased concentrations of LA in goat plasma and fertility in sperm, indicating that it has the ability to resist rumen biohydrogenation ( 82 ). Similarly, supplementation of CLA in the diets improved reproductive performance in dairy cows ( 83 ).…”
Section: Effects Of Diets Fas On Semen Qualitymentioning
confidence: 99%
“…It has been suggested that in ruminants, rumen microbes may hinder the transfer of dietary LA to semen because they hydrogenate LA ( 81 ). However, recent studies have shown that feeding additional LA results in significantly increased concentrations of LA in goat plasma and fertility in sperm, indicating that it has the ability to resist rumen biohydrogenation ( 82 ). Similarly, supplementation of CLA in the diets improved reproductive performance in dairy cows ( 83 ).…”
Section: Effects Of Diets Fas On Semen Qualitymentioning
confidence: 99%